Orographic rainfall during southwest monsoon : A dynamic climatological study - RAY, K. C. SINHA; DE, U. S.; CHELLAPA, R. (MAUSAM, 1982)
A two dimensional dynamical model for orographic rainfall developed earlier (Sarker 1966-67) was modified to include cases of partially saturated airstream in the vertical. In the present investigation an attempt has been made to isolate the steady orographic rainfall from the total precipitation over uneven terrain and to explain the spatial and diurnal variation of rainfall during the southwest monsoon season over the Western Ghats and over Khasi and Jaintia hills.